2007
DOI: 10.1021/jp073823k
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain Conformation of the M2 Transmembrane Peptide Proton Channel of Influenza A Virus from 19F Solid-State NMR

Abstract: The M2 transmembrane peptide (M2TMP) of the influenza A virus forms a tetrameric helical bundle that acts as a proton-selective channel important in the viral life cycle. The side-chain conformation of the peptide is largely unknown and is important for elucidating the proton-conducting mechanism and the channel stability. Using a 19F spin diffusion NMR technique called CODEX, we have measured the oligomeric states and interhelical side chain-side chain 19F-19F distances at several residues using singly fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(115 citation statements)
references
References 32 publications
10
101
4
Order By: Relevance
“…Moreover, one of the Trp41 residues flipped to the t90 conformer, as found in the crystal structures (9,24,55), during this simulation. This is consistent with another very long simulation study in which all four Trp41 residues eventually flipped to the t90 conformation (32), experimental support of the t90 conformation (9,12,24,55,56), and our own PMF calculation of the Trp41 χ 2 dihedral angle rotation discussed earlier in this paper. Therefore, to facilitate the equilibration, the remainder of the Trp41 side chains were manually rotated from the t-105 rotamer to the t90 rotamer.…”
Section: Methods and Simulation Detailssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, one of the Trp41 residues flipped to the t90 conformer, as found in the crystal structures (9,24,55), during this simulation. This is consistent with another very long simulation study in which all four Trp41 residues eventually flipped to the t90 conformation (32), experimental support of the t90 conformation (9,12,24,55,56), and our own PMF calculation of the Trp41 χ 2 dihedral angle rotation discussed earlier in this paper. Therefore, to facilitate the equilibration, the remainder of the Trp41 side chains were manually rotated from the t-105 rotamer to the t90 rotamer.…”
Section: Methods and Simulation Detailssupporting
confidence: 93%
“…S3) (the equilibration starting from the t-105 rotamer of Trp41 because in the NMR structure 2L0J does not yield a stable protein structure within 200-ns simulation). Our decision to change to the t90 rotamer of Trp41 is supported by crystal structures (9,24,55), SSNMR measurements (12,56), as well as long all-atom MD simulations (32), the latter showing that all four Trp41 residues flipped from the t-105 to the t90 rotamer after 500 ns. To further address this issue, we also calculated the PMF (Fig.…”
Section: Am2 Channel Has a Low Conduction Rate In The Inactivatedmentioning
confidence: 82%
“…Identifying proper monomer structures greatly reduces the conformation space needed to be searched for corresponding oligomer structures. By clustering the determined oligomers based on total potential energies and crossing angles, we found that the M2TMP tetramer has strong preference of being left-handed, placing Ser31, His37, and Trp41 in the pore region, which is in good agreement with the previously determined structure [14,42] and the recent X-ray structure [6]. However, based on the χ 2 distributions of His37 and Trp41, four different conformations were identified.…”
Section: Discussionsupporting
confidence: 85%
“…These conformations yields different distances between His37 (i) and Trp41 (i+1) as well as between Trp41 (i) and Trp41 (i+1) , which dictates the relative orientations of both residues inside the pore; for example, based on PDB:1NYJ, these distances are (3.8 Å, 11.7 Å) in (t60,t90), (3.6 Å, 11.4 Å) in (t-160,t90), (3.8 Å, 5.1 Å) in (t-160,t-105), and (3.6 Å, 5.1 Å) in (t60,t-105), where the first one is for His37 (i) and Trp41 (i+1) and the second one for Trp41 (i) and Trp41 (i+1) . Three conformations corresponding to (t-160,t90), (t-160,t-105), and (t60,t90) have been determined by 19 F SSNMR [42], REDOR SSNMR [14] and MD simulations [43], respectively.…”
Section: M2tmpmentioning
confidence: 99%
“…All structures agreed on the relative positions of pore-facing versus lipid-facing side chains; however, key differences exist about the rotameric states of His37 and Trp41. 17,30,31,84 It is worth noting that side chain conformations cannot be obtained from orientedmembrane SSNMR experiments, as they only measure backbone NAH bond orientations. The His37 and Trp41 rotamers in the recent oriented-membrane SSNMR structure of M2(22-62) were based on computational modeling.…”
Section: High-resolution Structures Of M2mentioning
confidence: 99%